Strengthening capacity and networking for forage disease identification and surveillance in eastern and southern Africa - Dawit, Woubit; Mulatu, Fikerte; Hirko, Mignote; Negawo, Alemayehu T. (International Livestock Research Institute, 2025)
This report summarizes the outcomes of the regional training workshop held at the International Livestock Research Institute (ILRI) from 24–26 June 2025. The workshop focused on strengthening capacity and fostering networks for forage disease identification and surveillance in Eastern and Southern Africa. It was conducted under the Areas of Work on Plant Health and Mycotoxin-Safe Crops of the CGIAR Sustainable Farming Science Program, and the Area of Work on Germplasm Health under the CGIAR Genebanks Accelerator.